Potentially inappropriate prescribing in older hospitalized Dutch patients according to the STOPP/START criteria v2: a longitudinal study. - Damoiseaux-Volman, Birgit A.; Medlock, Stephanie; Raven, Kimmy; Sent, Danielle; Romijn, Johannes A.; van der Velde, Nathalie; Abu-Hanna, Ameen (European Journal of Clinical Pharmacology, 2021)
Purpose: To investigate prevalence, independent associations, and variation over time of potentially inappropriate prescriptions in a population of older hospitalized patients. Methods: A longitudinal study using a large dataset of hospital admissions of older patients (≥ 70 years) based on an electronic health records cohort including data from 2015 to 2019. Potentially inappropriate medication (PIM) and potential prescribing omission (PPO) prevalence during hospital stay were identified based on the Dutch STOPP/START criteria v2. Univariate and multivariate logistic regression were used for analyzing associations and trends over time. Results: The data included 16,687 admissions. Of all admissions, 56% had ≥ 1 PIM and 58% had ≥ 1 PPO. Gender, age, number of medications, number of diagnoses, Charlson score, and length of stay were independently associated with both PIMs and PPOs. Additionally, number of departments and number of prescribing specialties were independently associated with PIMs. Over the years, the PIM prevalence did not change (OR = 1.00, p =.95), whereas PPO prevalence increased (OR = 1.08, p <.001). However, when corrected for changes in patient characteristics such as number of diagnoses, the PIM (aOR = 0.91, p <.001) and PPO prevalence (aOR = 0.94, p <.001) decreased over the years. Conclusion: We found potentially inappropriate prescriptions in the majority of admissions of older patients. Prescribing relatively improved over time when considering complexity of the admissions. Nevertheless, the high prevalence shows a clear need to better address this issue in clinical practice. Studies seeking effective (re)prescribing interventions are warranted.